Atlas of Imaging in Infertility : A Complete Guide Based in Key Images - de Souza, Luis Ronan Marquez Ferreira; De Nicola, Ana Luisa Alencar; De Nicola, Harley (Springer International Publishing : Imprint: Springer, 2017)
This atlas gathers the most frequent imaging findings concerning alterations that cause infertility in both males and in females. Also, it discusses how the images should be analyzed and described, to serve as a guide for the physicians who request and perform these imaging tests. Infertility is a highly prevalent condition - about 10% of couples are infertile with males and females equally affected. This book offers professionals dealing with infertility, including endocrinologists, gynecologists and urologists, a useful guide to the diagnostic imaging tests that are essential in treating these patients. The Atlas of Imaging in Infertility is a valuable resource for physicians from different specialties managing cases of infertility.- Resumé vydavatel
Keywords: neplodnost; diagnostické zobrazovací metody; infertility; diagnostic imaging methods; elektronické knihy; atlasy; electronic books; atlases